The relationship between taxpayer compliance and taxpayer compulsion on optimizing regional tax revenues in three cities in East Java Province - Shinta Awalia Rizky Nugrahani; Fadillah Putra; Siti Rochmah (Faculty of Law, Universitas Pekalongan, 2023)
This research aims to investigate the relationship between taxpayer compliance and taxpayer compulsion to optimize local tax revenues in three cities in East Java Province, namely Madiun City, Mojokerto and Probolinggo. Collective action is used in this research as a theoretical lens that can explore in depth the actions taken by local governments in an effort to optimize tax revenues. A quantitative approach is used to test the relationship between variables through hypothesis testing based on statistical power. A total of 468 respondents was determined based on the results of the Slovin formula calculation. The findings of this research indicate that taxpayer compliance and taxpayer compulsion in the three cities in East Java Province have a positive and significant effect on the optimization of regional tax revenues. This of course has implications for local revenue (PAD) which can be optimized by regional governments through regional tax revenues. Theoretical and practical implications in this research have also been discussed comprehensively based on the research findings.